A Study on the Application of Natural Antioxidant Lignan in Boiled and Smoked and Boiled Sausages. Issue 2 (March 2020) - Gao, Qianqian; Wang, Yingchen; Kuang, Ming; Zhang, Wenying
Abstract: With fresh carp meat and black fungus as the main raw materials, black fungus and pork sausages with fish flavor and rich nutrition were made through reasonable processing based on the optimal process formula; the color, fat oxidation, odor, and rancidity of the product during storage were investigated after adding different amounts of natural antioxidant lignan; and the comparison with the blank control and analysis were carried out. The results show that the addition of 0.075% lignan had the best antioxidant effect. The TBA value and acid value of lignan-added sausages were significantly lower than those without lignan.